Neurogenic Pulmonary Edema Following a Seizure: A Case Report and Literature Review - Mostafa Suhail Najim; Riyadh Ali Mohammed Hammamy; Sreethish Sasi (Case Reports in Neurological Medicine)
Acute pulmonary edema is one of the frequent causes of dyspnea encountered in everyday practice. It is broadly attributed to be either cardiogenic or noncardiogenic. It is usually treated with diuretics in addition to other medications depending on the underlying pathology. Here, we report a case of a female patient who presented with shortness of breath after developing a seizure. Further investigations excluded cardiogenic etiology and showed critically low phenytoin level. It improved within 48 h of supportive care without giving diuretics favoring the diagnosis of neurogenic pulmonary edema as the primary pathology. The goal of our case report is to keep neurogenic pulmonary edema in mind, and hence provide the appropriate management, when dealing with similar cases.